Crystal structure of a conserved domain in the intermembrane space region of the plastid division protein ARC6. (29th October 2015) - Kumar, Nitin; Radhakrishnan, Abhijith; Su, Chih‐Chia; Osteryoung, Katherine W.; Yu, Edward W.
Abstract: The chloroplast division machinery is composed of numerous proteins that assemble as a large complex to divide double‐membraned chloroplasts through binary fission. A key mediator of division‐complex formation is ARC6, a chloroplast inner envelope protein and evolutionary descendant of the cyanobacterial cell division protein Ftn2. ARC6 connects stromal and cytosolic contractile rings across the two membranes through interaction with an outer envelope protein within the intermembrane space (IMS). The ARC6 IMS region bears a structurally uncharacterized domain of unknown function, DUF4101, that is highly conserved among ARC6 and Ftn2 proteins. Here we report the crystal structure of this domain from Arabidopsis thaliana ARC6. The domain forms an α/β barrel open towards the outer envelope membrane but closed towards the inner envelope membrane. These findings provide new clues into how ARC6 and its homologs contribute to chloroplast and cyanobacterial cell division. Abstract : 5D9R